Enhancement of microwave absorption bandwidth of MXene nanocomposites through macroscopic design. Issue 8 (5th August 2020) - Bora, Pritom J.; Suresh Kumar, T. R.; Tan, Daniel Q.
Abstract : MXene, the new family of two-dimensional materials having numerous nanoscale layers, is being considered as a novel microwave absorption material. However, MXene/functionalized MXene-loaded polymer nanocomposites exhibit narrow reflection loss (RL) bandwidth (RL less than or equal to −10 dB). In order to enhance the microwave absorption bandwidth of MXene hybrid-matrix materials, for the first time, macroscopic design approach is carried out for TiO2 -Ti3 C2 Tx MXene and Fe3 O4 @TiO2 -Ti3 C2 Tx MXene hybrids through simulation. The simulated results indicate that use of pyramidal meta structure of MXene can significantly tune the RL bandwidth. For optimized MXene hybrid-matrix materials pyramid pattern, the bandwidth enhances to 3–18 GHz. Experimental RL value well matched with the simulated RL. On the other hand, the optimized Fe3 O4 @TiO2 -Ti3 C2 Tx hybrid exhibits two specific absorption bandwidths (minimum RL value - −47 dB). Compared with other two-dimensional nanocomposites such as graphene or Fe3 O4 -graphene, MXene hybrid-matrix materials show better microwave absorption bandwidth in macroscopic pattern.